2021
DOI: 10.1186/s11689-021-09384-z
|View full text |Cite
|
Sign up to set email alerts
|

Current neurologic treatment and emerging therapies in CDKL5 deficiency disorder

Abstract: Background CDKL5 deficiency disorder (CDD) is associated with refractory infantile onset epilepsy, global developmental delay, and variable features that include sleep, behavioral disturbances, and movement disorders. Current treatment is primarily symptom-based and informed by experience in caring for this population. Methods We describe medication and non-medication approaches to treatment of epilepsy and additional key neurologic symptoms (sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Aside from nutritional difficulties affecting growth, a gastrostomy tube may improve caregiver quality of life, assist in the administration of fluids and/or a ketogenic diet and, through compliance with medications and/or ketogenic diet, may reduce seizure burden ( 73 , 74 ). A review of patients from the CDKL5 Disorder Database found that 20.7% of individuals were fed exclusively by gastrostomy or nasogastric tube ( 19 ) but this prevalence may be as high as 43% among individuals with CDD, following analysis of patients based in the United States of America ( 75 ) (154 individuals identified from data held by Centers of Excellence and 40 identified from the NIH's Natural History of Rett and Related Disorders database). In a smaller study on quality of life domains for those with CDD, as many as 56% (14/25 surveyed from the CDKL5 international registry) had a gastrostomy ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aside from nutritional difficulties affecting growth, a gastrostomy tube may improve caregiver quality of life, assist in the administration of fluids and/or a ketogenic diet and, through compliance with medications and/or ketogenic diet, may reduce seizure burden ( 73 , 74 ). A review of patients from the CDKL5 Disorder Database found that 20.7% of individuals were fed exclusively by gastrostomy or nasogastric tube ( 19 ) but this prevalence may be as high as 43% among individuals with CDD, following analysis of patients based in the United States of America ( 75 ) (154 individuals identified from data held by Centers of Excellence and 40 identified from the NIH's Natural History of Rett and Related Disorders database). In a smaller study on quality of life domains for those with CDD, as many as 56% (14/25 surveyed from the CDKL5 international registry) had a gastrostomy ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown reductions in seizures with soticlestat and fenfluramine. Ataluren has not shown efficacy in treating CDD [ 9 , 31 ]. It is worth mentioning that various attempts are being made to develop disease-modifying therapies that address the neurobiology and developmental abnormalities of CDKL5 disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures range from tonic, tonic-clonic and myoclonic spasms, or seizures with no clear pattern. Seizures initially respond to a range of broad-spectrum anti-epileptic treatments [ 27 ] but often return for life and may be in a different form [ 20 , 21 ]. Other seizure modulators used include cannabis derivatives and ketogenic diets, but their effectiveness in reducing seizures is limited and wanes over time [ 27 ].…”
Section: Cdkl5 Deficiency Disorder (Cdd) Clinical Phenotype and Geneticsmentioning
confidence: 99%
“…Seizures initially respond to a range of broad-spectrum anti-epileptic treatments [ 27 ] but often return for life and may be in a different form [ 20 , 21 ]. Other seizure modulators used include cannabis derivatives and ketogenic diets, but their effectiveness in reducing seizures is limited and wanes over time [ 27 ]. Seizure frequency, the level of functional impairment and the anti-seizure medication regimen all influence quality of life for CDD individuals [ 28 ].…”
Section: Cdkl5 Deficiency Disorder (Cdd) Clinical Phenotype and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation